Peningkatkan Hasil Belajar Matematika Siswa dengan Pemanfaatan Model Lasswel Communication - Amelia Shofa (Journal Mathematics Education Sigma [JMES], 2022)
Abstract. This article describes efforts to improve students' mathematics learning outcomes using the Lasswel Communication model. This article aims to find out whether or not there is an increase in students' mathematics learning outcomes using the Lasswel Communication Model in class VII SMP IT Al - Manah Mamiregi. The data presented in this article is sourced from classroom action research during January to February 2018. The results in the first cycle were 17 students who achieved a learning mastery level (above 65%) and classically 53%. While in the second cycle there was an increase, namely there were 26 students achieving a level of completeness above 65% and classically by 81%. Students' difficulties in solving some of the problems that arise include students still having difficulty understanding questions, students still having difficulty performing arithmetic operations on algebraic forms, simplifying algebraic forms and students still not being able to do mathematical calculations correctly.Abstrak. Artikel ini menggambarkan tentang upaya meningkatkan hasil belajar matematika siswa dengan model Lasswel Communication. Artikel ini bertujun untuk mengetahuinya ada atau tidaknya peningkatan hasil belajar Matematika siswa dengan menggunakan Model Lasswel Communication di kelas VII SMP IT Al – Manah Mamiregi. Data yang dipaparkan dalam artikel ini bersumber dari penelitian tindakan kelas selama bulan Januari sampai Februari 2018. hasil pada siklus I terdapat 17 orang siswa yang mencapai tingkat ketuntasan belajar (diatas 65%) dan secara klasikal sebesar 53%. Sedangkan pada siklus II terjadi peningkatan yaitu terdapat 26 orang siswa mencapai tingkat ketuntasan diatas 65% dan secara klasikal sebesar 81%. Kesulitan siswa dalam menyelesaikan beberapa persoalan yang dimunculkan antara lain siswa masih mengalami kesulitan dalam memahami soal, siswa masih mengalami kesulitan dalam melakukan operasi hitung bentuk aljabar, menyederhanakan bentuk aljabar dan siswa masih kurang mampu melakukan perhitungan matematika secara benar.